2020
DOI: 10.18203/issn.2454-5929.ijohns20205646
|View full text |Cite
|
Sign up to set email alerts
|

Is elongated styloid process a potential forewarning for failure in oral submucous fibrosis management?

Abstract: <p class="abstract">Oral submucous fibrosis is a widespread, premalignant disorder causing severe difficulty in mastication and speech. With high rate of malignant conversion, it demands aggressive surgical therapy followed by mandatory long-term physiotherapy. An elongated styloid process, if present, could pose a strong hindrance to movement of mandible, leading to complete relapse of trismus in such cases. The purpose of this report is to elaborate on such co-existence in patients having oral submucou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Importantly, in the present study, there is a predominance of ESP present among OSMF patients. Similarly, Patel et al concluded in their case report that ESP can be a restricting factor in treating OSMF patients, and Shivakumar et al also concluded that ESP can influence progressive OSMF [ 24 ]. The clinical manifestations of stylalgia, which is the pain experienced by patients due to ESP, frequently result in the patient experiencing excruciating pain and suffering because of incorrect diagnoses and unsuccessful prior treatments, even from skilled medical professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in the present study, there is a predominance of ESP present among OSMF patients. Similarly, Patel et al concluded in their case report that ESP can be a restricting factor in treating OSMF patients, and Shivakumar et al also concluded that ESP can influence progressive OSMF [ 24 ]. The clinical manifestations of stylalgia, which is the pain experienced by patients due to ESP, frequently result in the patient experiencing excruciating pain and suffering because of incorrect diagnoses and unsuccessful prior treatments, even from skilled medical professionals.…”
Section: Discussionmentioning
confidence: 99%